Harnessing Recent Advances in Synthetic DNA and Electroporation Technologies for Rapid Vaccine Development Against COVID-19 and Other Emerging Infectious Diseases - Xu, Ziyang; Patel, Ami; Tursi, Nicholas J.; Zhu, Xizhou; Muthumani, Kar; Kulp, Daniel W.; Weiner, David B. (Frontiers in Medical Technology, 2020)
DNA vaccines are considered as a third-generation vaccination approach in which antigenic materials are encoded as DNA plasmids for direct in vivo production to elicit adaptive immunity. As compared to other platforms, DNA vaccination is considered to have a strong safety profile, as DNA plasmids neither replicate nor elicit vector-directed immune responses in hosts. While earlier work found the immune responses induced by DNA vaccines to be sub-optimal in larger mammals and humans, recent developments in key synthetic DNA and electroporation delivery technologies have now allowed DNA vaccines to elicit significantly more potent and consistent responses in several clinical studies. This paper will review findings from the recent clinical and preclinical studies on DNA vaccines targeting emerging infectious diseases (EID) including COVID-19 caused by the SARS-CoV-2 virus, and the technological advancements pivotal to the improved responses - including the use of the newer intradermal electroporation (ID-EP) technology, DNA-encoded adjuvant cytokines, and DNA-launched nano-vaccine technology. With continuous advancement over the past three decades, the DNA approach is now well-poised to develop vaccines against COVID-19, as well as other EIDs.